GesturePod: Enabling on-device gesture-based interaction for white cane users - Patil, Shishir G.; Dennis, Don Kurian; Pabbaraju, Chirag; Shaheer, Nadeem; Simhadri, Harsha; Seshadri, Vivek; Varma, Manik; Jain, Prateek (ACM Symposium on User Interface Software and Technology, 2019)
People using white canes for navigation find it challenging to concurrently access devices such as smartphones. Building on prior research on abandonment of specialized devices, we explore a new touch free mode of interaction wherein a person with visual impairment can perform gestures on their existing white cane to trigger tasks on their smartphone. We present GesturePod, an easy-to-integrate device that clips on to any white cane, and detects gestures performed with the cane. With GesturePod, a user can perform common tasks on their smartphone without touch or even removing the phone from their pocket or bag. We discuss the challenges in building the device and our design choices. We propose a novel, efficient machine learning pipeline to train and deploy the gesture recognition model. Our in-lab study shows that GesturePod achieves 92% gesture recognition accuracy and can help perform common smartphone tasks faster. Our in-wild study suggests that GesturePod is a promising tool to improve smartphone access for people with VI, especially in constrained outdoor scenarios.